Calendar of the fine rolls of the reign of Henry III : preserved in the National Archives. - Dryburgh, Paul; Hartland, Beth; Ciula, Arianna (Boydell Press ; Boydell & Brewer, 2008)
First ever translation of the Fine Rolls makes documents of crucial importance for study of the period fully available for the first time.